2019
DOI: 10.1371/journal.pone.0220382
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced anti-tumor immunotherapy by dissolving microneedle patch loaded ovalbumin

Abstract: The skin is a very suitable organ for the induction of immune responses to vaccine antigens. Antigen delivery systems to the skin by needle and syringe directly deposit the antigen into the epidermal-dermal compartment, one of the most immunocompetent sites due to the presence of professional antigen-presenting cells aimed at the induction of antigen-specific T cells. In this study, we analyzed the amount of ovalbumin as an antigen delivered to the skin by a microneedle. When ovalbumin protein as an antigen wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…In this regard, using MNs can be a good choice to achieve maximum delivery while limiting side effects. To this end, Lee et al used a MN containing the antigen OVA as an immune-stimulating antigen delivery system to activate antitumor immunity into the skin of mice [127]. They observed that the OVA-loaded MN patch J o u r n a l P r e -p r o o f exhibited a significantly reduced tumor size (78.75±30.1 mm 3 ) and weight (0.82±0.5 gr) compared to a control patch, which had a tumor size and weight of 249.67±39.1 mm 3 and 2.33±0.9 g, respectively.…”
Section: Mns For Effective Delivery Of Other Cancer Vaccinesmentioning
confidence: 99%
“…In this regard, using MNs can be a good choice to achieve maximum delivery while limiting side effects. To this end, Lee et al used a MN containing the antigen OVA as an immune-stimulating antigen delivery system to activate antitumor immunity into the skin of mice [127]. They observed that the OVA-loaded MN patch J o u r n a l P r e -p r o o f exhibited a significantly reduced tumor size (78.75±30.1 mm 3 ) and weight (0.82±0.5 gr) compared to a control patch, which had a tumor size and weight of 249.67±39.1 mm 3 and 2.33±0.9 g, respectively.…”
Section: Mns For Effective Delivery Of Other Cancer Vaccinesmentioning
confidence: 99%
“…Traditional vaccinations cause pain, generate sharp waste, require cold storage, and bypass the immune system of the skin. In contrast, several studies have demonstrated that MNs cause indiscernible pain (78)(79)(80), minimize the generation of sharp waste and associated hazard, stabilize proteins at room temperature eliminating the need of cold storage (81)(82)(83)(84)(85), and produce a superior robust immune response by targeting ED and dermis region of skin rich with immune cells (6,(86)(87)(88)(89)(90)…”
Section: Vaccine Developmentmentioning
confidence: 99%
“…The reduced height of the MN and adjustments in geometric conformation allow painless application to the epidermis or close to the dermis without reaching the pain receptors and allow the administration of substances of different lipophilicity [10,11]. In addition, through technological modifications that have enabled the advancement from metallic MN to polymeric MN design, MNs have been named as one of the top ten emerging technologies in 2020 and have become a market promise for the possibility of drug, protein, and hormone delivery [12][13][14]. The global transdermal drug delivery system (TDDS) market is projected to be worth USD 8.4 billion by 2027, at a compound annual growth rate (CAGR) of 4.3% [15], and projections for the global market for MNs in drug delivery systems comprise a CAGR of 6.6% between 2020 and 2030, representing an estimated market value of USD 1.2 billion by 2030 [16].…”
Section: Introductionmentioning
confidence: 99%